8x(3x+2)=-5(2-x)+3

Simple and best practice solution for 8x(3x+2)=-5(2-x)+3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 8x(3x+2)=-5(2-x)+3 equation:


Simplifying
8x(3x + 2) = -5(2 + -1x) + 3

Reorder the terms:
8x(2 + 3x) = -5(2 + -1x) + 3
(2 * 8x + 3x * 8x) = -5(2 + -1x) + 3
(16x + 24x2) = -5(2 + -1x) + 3
16x + 24x2 = (2 * -5 + -1x * -5) + 3
16x + 24x2 = (-10 + 5x) + 3

Reorder the terms:
16x + 24x2 = -10 + 3 + 5x

Combine like terms: -10 + 3 = -7
16x + 24x2 = -7 + 5x

Solving
16x + 24x2 = -7 + 5x

Solving for variable 'x'.

Reorder the terms:
7 + 16x + -5x + 24x2 = -7 + 5x + 7 + -5x

Combine like terms: 16x + -5x = 11x
7 + 11x + 24x2 = -7 + 5x + 7 + -5x

Reorder the terms:
7 + 11x + 24x2 = -7 + 7 + 5x + -5x

Combine like terms: -7 + 7 = 0
7 + 11x + 24x2 = 0 + 5x + -5x
7 + 11x + 24x2 = 5x + -5x

Combine like terms: 5x + -5x = 0
7 + 11x + 24x2 = 0

Begin completing the square.  Divide all terms by
24 the coefficient of the squared term: 

Divide each side by '24'.
0.2916666667 + 0.4583333333x + x2 = 0

Move the constant term to the right:

Add '-0.2916666667' to each side of the equation.
0.2916666667 + 0.4583333333x + -0.2916666667 + x2 = 0 + -0.2916666667

Reorder the terms:
0.2916666667 + -0.2916666667 + 0.4583333333x + x2 = 0 + -0.2916666667

Combine like terms: 0.2916666667 + -0.2916666667 = 0.0000000000
0.0000000000 + 0.4583333333x + x2 = 0 + -0.2916666667
0.4583333333x + x2 = 0 + -0.2916666667

Combine like terms: 0 + -0.2916666667 = -0.2916666667
0.4583333333x + x2 = -0.2916666667

The x term is 0.4583333333x.  Take half its coefficient (0.2291666667).
Square it (0.05251736113) and add it to both sides.

Add '0.05251736113' to each side of the equation.
0.4583333333x + 0.05251736113 + x2 = -0.2916666667 + 0.05251736113

Reorder the terms:
0.05251736113 + 0.4583333333x + x2 = -0.2916666667 + 0.05251736113

Combine like terms: -0.2916666667 + 0.05251736113 = -0.23914930557
0.05251736113 + 0.4583333333x + x2 = -0.23914930557

Factor a perfect square on the left side:
(x + 0.2291666667)(x + 0.2291666667) = -0.23914930557

Can't calculate square root of the right side.

The solution to this equation could not be determined.

See similar equations:

| 1270=.15x | | -5x-13x+3x=-25 | | -5x-13x+3x=25 | | 2x+y-4= | | 3+5m-4-8m=-8(m-3)+2(m-8) | | 8-3=5 | | 2+2-2=2+2-2+2 | | 24*x=96 | | 24xy=96 | | y(y+1)=20 | | (x+5)(x+5)=16 | | 9(c-1)=6(b+2)-a | | 77.94-5.8+201.681= | | 2x^2-36x+162=32 | | 10a^2-27ab+5b= | | 9(n-1)=6(n+2) | | x-7=3x | | 3(x+4)=(3x+12) | | 9x-1(4x-1)=2 | | 9x+3(-3x-5)=-12-3x | | 8x-7-7x-7=8x-7x-17 | | -7b+4+5b=-3b+9 | | 2(4x+7)=3+2x+2 | | 4x^2+2x-6= | | (5y-1)(23y-1)= | | 5x^2=27 | | x^2+3x^2=x^2 | | -11x+9=-12+13 | | 6x-8=3x | | 1x-9= | | 4x-y=-10 | | t(t-2)-3t(t-2)=0 |

Equations solver categories